Female sexual dysfunction among married women in the Gaza Strip: an internet-based survey - Maasoumi, Raziyeh; Elsous, Aymen; Hussein, Hawawu; Taghizadeh, Ziba; Baloushah, Suha (Annals of Saudi medicine, 2019)
Since sexual function is an important element of human life, sexual dysfunction may negatively affect the quality of life for both males and females. It is a widespread public health problem that is inadequately studied in the Arab world. Determine the prevalence of female sexual dysfunction (FSD) and associated factors in all women who sought reproductive health services in the community and who were in an active sexual relationship. A cross-sectional survey. Community. Married Palestinian women living in the Gaza strip in Palestine who were aged from 18-60 years old and could use the internet volunteered to participate during routine health visits. We used the Arabic version of the Female Sexual Function Index, which is comprised of six domains: desire, arousal, lubrication, orgasm, satisfaction, and pain. The data were analyzed descriptively and by univariate and multiple logistic regression analysis. Frequency of FSD and association with demographic, socioeconomic and clinical factors. 385 married women. The prevalence of FSD was 61% (n=235). Of those, 26.4% (101/385) had desire disorder, 20.2% (47/235) had arousal disorder, 18.4% (101/385) had orgasm disorder, 6.7% (26/385), 79% (304/385), and 21.2% (82/385) had lubricant disorder, pain disorder, and satisfaction, respectively. Logistic regression analysis showed that independent factors associated with FSD were parity (OR: 2.068; CI 95%: 1.047-3.985; P<.05), marriage dissatisfaction (OR: 6.299; CI 95%: 2.879-13.781; P<.001), and living in stressful conditions (OR: 2.181; CI 95%: 1.380-3.448; P<.001). There was no evidence of statistically significant associations between FSD and polygamy, intercourse frequency, wife's age, wife's job, husband's age, husband's job, education, abortion history, number of children, marital duration and using of family planning methods. FSD was common in women participating in our survey. More research on the effect of sexual dysfunction on quality of life is recommended as well as research on the awareness of the presence of dysfunction in women. The use of an internet survey was the major limitation of the study. Findings may not be generalizable. Further studies are needed to include women who do not have internet access. None.